(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2024)
The present study describes two occurrences of clam shrimps (“Conchostraca”). Following a form-based classification of Schneider et al. (2005, 2022) and Schneider & Scholze (2018), the conchostracans have been classified as Pseudestheria form Oberbozen and Pseudestheria form Le Fraine. They come from the Guncina and Tregiovo formations, repectivey. These units are part of the northern Athesian Volcanic Group, North Italy. All of this material were obtained from grey coloured, fine-grained siliciclastic, lacustrine deposits of Kungurian (late Cisuralian, late Early Permian) age. Their carapace valves in lateral view are marked by concentric ribs. Often, growth lines can be observed to decrease in their preservation towards the umbonal area of the valve. An open nomenclature is applied to the taxonomy at the species level herein, because of either limited number of individuals or a plastic deformation due to tectonics. So far, the records reported herein are restricted geographically and stratigraphically to respective single occurrences. Further studies are recommended to establish their full biostratigraphic ranges.